2009
DOI: 10.1016/j.amepre.2009.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal Cancer Screening by Primary Care Physicians

Abstract: Background-Primary care physicians (hereafter, physicians) play a critical role in the delivery of colorectal cancer (CRC) screening in the U.S. This study describes the CRC screening recommendations and practices of U.S. physicians and compares them to findings from a 1999-2000 national provider survey.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
168
7
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 188 publications
(189 citation statements)
references
References 42 publications
11
168
7
2
Order By: Relevance
“…26 Though our study suggests that primary care providers often discuss constructs related to CRC screening, discussions were often limited in scope. As in other US-based studies, [27][28][29][30] study providers demonstrated a clear preference for screening colonoscopy over flexible sigmoidoscopy or FOBT, which were discussed in a minority of visits.…”
Section: Discussionmentioning
confidence: 92%
“…26 Though our study suggests that primary care providers often discuss constructs related to CRC screening, discussions were often limited in scope. As in other US-based studies, [27][28][29][30] study providers demonstrated a clear preference for screening colonoscopy over flexible sigmoidoscopy or FOBT, which were discussed in a minority of visits.…”
Section: Discussionmentioning
confidence: 92%
“…Screening colonoscopy (SC) is advocated by many professional organizations and is increasingly common in clinical practice [2][3][4][5][6] . However, there are important concerns about how age, sex, and comorbidity moderate the effectiveness of SC.…”
Section: Introductionmentioning
confidence: 99%
“…10 In a national survey of PCPs, Klabunde et al 11 found that 30% reported some mechanism to prompt PCPs, 15% used patient reminders, and only 12% received reports of CRCS rates for their patient panel. Investigators who analyzed practice performance data from a network of PCPs using a common electronic health record described several strategies used by high-performing practices, including prioritizing performance, progress note templates, wellness visits combined with an opportunistic approach to screening, sigmoidoscopy for self-paying patients, and patient activation through a variety of repeated screening messages.…”
mentioning
confidence: 99%